Uma Plataforma de Desenvolvimento de Sistemas Empresariais baseada em modelos e regras de negócio - PURIFICAÇÃO, Carlos Eugênio Palma da (2016)
Organizations need to align information systems with its rules and business processes. These systems are needed in strategic data management and maintenance in order to achieve the business goals and create competitive opportunities. However, in this type of organization, financial resources are scarce in the initial phase of its operations, which makes it critical that their information systems can be built faster and less costly. Generally, in these company’s information systems, the business rules and processes are described in natural language documents disassociated from the system and later implemented directly in the software source code. This practice can lead to high maintenance costs and difficulty in adapting systems to the needs of changing business rules, because it usually involves some source-code modification by information technology specialized teams. In addition, the translation of business rules by these professionals, can lead to loss of the original rule semantics, resulting in erroneous implementation of the original business analyst intention. Similarly, user interaction model is usually implemented based on programming techniques, leaving it to developers to create and maintain the various system screens, capture events, navigation control and its interaction with organization business rules. This paper proposes a platform and a model-driven software development process for incorporating and maintaining business rules in a flexible manner, using the business language itself, but based on a formalism, as opposed to the use of a natural language and translating the rules to programming languages constructs, to allow the systems business rules to be quickly adapted and incorporated into the systems by business partners. The user interaction model is also formally defined to encompass the concepts of this interaction, and to allow its validation against business rules and its subsequent transformation into executable code. The proposed platform involves tooling and components, that along with a model-driven development process assists the user on defining the system conceptual model and generating the final application. Domain specific languages based on formal standards were designed to allow the definition of the system conceptual model covering view, structural, business and user interaction aspects in an integrated manner. A use case study illustrates the use of the proposed development model, wherein a sample application is modeled in its user interaction, structure and data input validation rules aspects. Subsequently it is shown how these models are subjected to a transformation process to generate the final application. The examples presented in the use case study show how it is possible validation of user input based on business rules using the proposed approach.